Visualizing Cyclic Adenosine Monophosphate in Cardiac Microdomains Involved in Ion Homeostasis - Dikolayev, Vladimir; Tuganbekov, Turlybek; Nikolaev, Viacheslav O. (Frontiers in Physiology, 2019)
3’,5’-cyclic adenosine monophosphate (cAMP) is a key second messenger that regulates function of proteins involved in ion homeostasis and cardiac excitation-contraction coupling. Over the last decade, it has been increasingly appreciated that cAMP conveys its numerous effects by acting in discrete subcellular compartments or “microdomains”. In this mini review, we describe how such localized signals can be visualized in living cardiomyocytes to better understand cardiac physiology and disease. Special focus is made on targeted biosensors that can be used to resolve second messenger signals within nanometers of cardiac ion channels and transporters. Potential directions for future research and the translational importance of cAMP compartmentalization are discussed.